Parallel faecal and organ Mycobacterium avium subsp. paratuberculosis culture of different productivity types of cattle - Pavlik, I; Matlova, L; Bartl, J; Svastova, P; Dvorska, L; Whitlock, R (Veterinary microbiology, 2000)
Faecal (at least 3 months before slaughtering) and organ examinations were carried out in 611 animals (497 dairy, 69 dual-purpose and 44 beef cattle) originating from eight paratuberculosis infected cattle herds. The diagnosis in cattle was established by routine intestinal culture (ileum and the adjacent lymph nodes) after slaughter. In selected 132 animals, post-mortem intensive culture was performed on tissue samples collected from the gastrointestinal tract (duodenum, jejunum, ileum, ileocecal valve, caecum, rectum) and the corresponding lymph nodes, submandibular, retropharyngeal, tracheobronchial, liver and supramammary lymph nodes, kidney, liver and spleen. In 251 (41.1%) of all 611 animals, Mycobacterium avium subspecies paratuberculosis could be isolated from the faeces; in 164 (65.7%) out of 251 shedding animals the infection was detected in the ileum and adjacent lymph nodes. The detection of M. paratuberculosis by routine intestinal culture of faecal culture positive animals varied from 46.0% in animals shedding 1 CFU (colony forming unit), to 94.7% in massive shedders. On the contrary, M. paratuberculosis was detected by routine intestinal culture in 92 (25.5%) of the 360 faecal culture negative animals. Shedding animals had significantly higher (P<0.01) number of organisms in their organs than non-shedding animals. During the intensive tissue cultivation from selected 132 animals, 72 (54.5%) of them were positive. For the negative animals, no significant difference was found between the detection rate in organs examined after slaughter with routine and intensive method. However, in the subgroup of tissue culture positive animals a highly significant difference (P<0.01) was found by intensive examination (83.0%) compared with the routine examination (60.4%). Out of 72 tissue culture positive animals 73.6% of them harboured M. paratuberculosis in the gastrointestinal tract, 16.7% in the gastrointestinal tract and the parenchymatous organs, tracheobronchial and mandibular lymph nodes. The rest of the 9.7% of the infection was detected in the lymph nodes of head and lungs. Our study concerning the distribution of M. paratuberculosis by intensive examinations revealed a minimum effect of breed and production type on localisation of the agent. Thus, the results suggest that in case of an active infection, M. paratuberculosis can be localised in different organs of animals irrespective of their breed or production type.
Keywords: Feces; Mycobacterium avium subsp. paratuberculosis; Intestines; Dairying; mužské pohlaví; Lymph Nodes; skot; paratuberkulóza; Paratuberculosis; střeva; nemoci skotu; ženské pohlaví; Culture Techniques; zvířata; feces; mlékárenství; kultivační techniky; Cattle; lymfatické uzliny; Cattle Diseases; Female; Male; Animals